Pengaruh Polivinilpirolidon K-30 terhadap Disolusi Ketoprofen dalam Sistem Dispersi Padat - Rieke Azhar; Muslim Suardi; Salman Umar (Jurnal Farmasi Higea, 2009)
Effects of polyvinylpyrrolidone K-30 on dissolution characteristics of solid dispersion systems have been studied. Solid dispersions were prepared by solvent method using several ratios of ketoprofen-polyvinylpyrrolidone K-30 as follows 1:9, 3:7, 5:5, 7:3, 9:1. Physical mixtures of ketoprofen-polyvinylpyrrolidone K-30 were used as a comparison. The solid dispersion systems and physical mixtures were evaluated for physicochemical properties and dissolution characteristics. Dissolution tests were measure with modified basket method using pH 7.2 phosphate buffer as dissolution medium. Samples were taken up after 5, 10, 15, 20, 30, 45, and 60 minutes. Results generally showed that solid dispersion system of ketoprofenpolyvinylpyrrolidone K-30 have a different physicochemical properties compared to physical mixtures and pure ketoprofen and exhibited better dissolution rate and dissolution efficiency of ketoprofen. Dissolution efficiency and dissolution rate constant of the solid dispersion system were 59.41%, and 1.66 mg/s, respectively.